SYSTEMATIC LITERATURE REVIEW : TREND PENELITIAN MODEL PEMBELAJARAN CONCEPTUAL LEARNING DI PERGURUAN TINGGI - Margareta Sinaga, Eka; Molliq Rangkuti, Yullita; Surya, Edy (SCHOOL EDUCATION JOURNAL PGSD FIP UNIMED, 2024)
This research aims at using appropriate learning models to help students avoid misconceptions and help students construct new knowledge through appropriate learning models. The method used is a systematic literature review taken from national journals and international journals. Search for library sources in this article via Google, SagePub, Science Direct, Emerald Insight, Hindawi, Springer, Taylor and Francis, and Wiley databases for 2013-2024. Based on the results of the study, it was found that the concept learning model is a learning model that has the view that students are not only required to be able to form concepts through classifying data, but they must also be able to form concepts using their own abilities. By using the concept learning model in the learning process, it is hoped that students' understanding of concepts will increase. The concept learning model is designed to teach concepts and help students more effectively learn the concepts of the material they are studying so that it can significantly help them in the process of improving their learning outcomes. This model is an efficient method of presenting structured and planned information from a wide range of topics for students at every level of development.